Lowering environmental costs of oil-palm expansion in Colombia - García Ulloa, J.; Sloan, S.; Pacheco, P.; Ghazoul, J.; Koh, L.P. (Wiley, 2012)
Colombia is the fifth largest producer of palm oil in the world. The country's government and oil‐palm farmers association target a sixfold increase of crude palm‐oil production by 2020. We model the impacts of expanding oil‐palm agriculture in Colombia through a spatially explicit scenario analysis. We demonstrate that the impacts of oil‐palm expansion (e.g., deforestation, conversion of natural savannahs) would be minimized by establishing new plantations on pasture lands, given the low environmental value and economic utility, and the high agricultural potential of this land use. Impacts of oil‐palm expansion on beef and dairy production could be compensated by improving productivity of pasture lands elsewhere. However, the profitability of oil‐palm production in these areas might suffer over the long term due to high land purchase costs.